Intrinsic Elastic Anisotropy of Westerly Granite Observed by Ultrasound Measurements, Microstructural Investigations, and Neutron Diffraction. Issue 1 (11th January 2021) - Lokajíček, T.; Vasin, R.; Svitek, T.; Petružálek, M.; Kotrlý, M.; Turková, I.; Onysko, R.; Wenk, H. R.
Abstract: Westerly granite (WG) has been generally accepted as an isotropic homogeneous rock. Here, we return to WG and observe significant elastic anisotropy using multidirectional ultrasonic sounding on spherical samples at pressures up to 400 MPa. Thermal treatment of WG leads to formation of microcracks that reduce elastic wave velocities and increase its elastic anisotropy. The 3D distribution of P‐wave velocities at low pressure is close to orthorhombic symmetry. Application of hydrostatic pressure closes most of thermally induced microcracks and decreases elastic anisotropy of WG, but at high pressure the anisotropy is practically reversed compared to low pressure: maximum P‐wave velocity direction at low pressures is near minimum velocity direction at high pressure and vice versa. To understand this effect, microstructures of the rock were investigated by optical and scanning electron microscopy. Preferred orientations of four major rock‐forming minerals—quartz, orthoclase, plagioclase, and biotite—were measured by time‐of‐flight neutron diffraction, which confirms significant crystal alignment. All these data were used to numerically model anisotropic elastic properties of WG. It is shown that WG possesses weak intrinsic elastic anisotropy related mainly to the preferred orientation of feldspars formed during igneous crystallization. Observed microcracks are mostly related to the cleavage planes of feldspars and biotite, and thus also demonstrate preferred orientation. Higher preheating temperatures produce larger quantity of longer microcracks. A numerical model shows that these microcracks act against the weak intrinsic elastic anisotropy of WG, and define the elastic anisotropy at low pressures. Key Points: Intrinsic anisotropy in Westerly granite is documented by ultrasonics on spheres, crystal preferred orientations by neutron diffraction and shape preferred orientation (SPO) explored with scanning electron microscopy Ultrasound experiments at different pressures and heating cycles document microfractures that appear to be dominantly along grain boundaries Adding crystal preferred orientations and SPO, we can predict elastic properties that agree with velocity measurements